The effect of incorporation of wheat bran on the quality of non-fried instant noodles / Nurbaizura Mat Adam - Mat Adam, Nurbaizura (2008)
The quality of non-fried instant noodles produced by addition of wheat bran was investigated. The quality of the non-fried instant noodles produced was compared with that of noodles made only of wheat flour (control). Tests were run on the samples to determine chemical composition (moisture, carbohydrate, fat, protein, crude fibre and ash), calorie content, physical properties (firmness and colour) and sensory attributes. Results shows that moisture (3.0% to 4.0%), protein (11% to 14.5%), fat (0.1% to 1.0%), crude fibre (0.6% to 4.5%) and ash (2% to 3.5%) content increased with addition of 10%, 30% and 50% wheat bran except for carbohydrate (82% to 77%). The calorie content of non-fried instant noodles increased (369 kcal to 383 kcal) with increasing addition of wheat bran. Addition of wheat bran also decreased the lightness (“L*” value) and yellowness (“b*” value) and increased the redness (“a*” value) of uncooked and cooked instant noodles. In addition, cooked noodles firmness (156 g/cm to 112 g/cm) decreased with increasing wheat bran content. Quantitative descriptive analysis (QDA) showed that the aftertaste and color intensity increased significantly